2019
DOI: 10.1080/17588928.2019.1598349
|View full text |Cite
|
Sign up to set email alerts
|

Some clarifications on neural noise and sensory sensitivities in Autism

Abstract: Ward (2018) has provided an elegant synthesis of the literature on the neural basis of individual differences in sensory sensitivity, and a useful proposed framework to guide future research. In this commentary clarify some of the issues raised by Ward (2018) surrounding neural noise and sensory sensitivities in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…What specific neural mechanisms might underpin low excitation across multiple sensory cortices in aphantasia? Our model fits broadly with neural noise theories from the autism literature which suggest that high levels of sensory sensitivity in people with autism are drivenat least in partby increased levels of neural noise (excitation) within sensory cortices (Milne, 2011;Rubenstein & Merzenich, 2003;Simmons, 2019;Simmons et al, 2009). This theory links neural noise with an increase in excitatory (e.g., glutamate) synaptic activity and a reduction of inhibitory (e.g., GABA) synaptic activity (e.g., Rubenstein & Merzenich, 2003;Wood et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…What specific neural mechanisms might underpin low excitation across multiple sensory cortices in aphantasia? Our model fits broadly with neural noise theories from the autism literature which suggest that high levels of sensory sensitivity in people with autism are drivenat least in partby increased levels of neural noise (excitation) within sensory cortices (Milne, 2011;Rubenstein & Merzenich, 2003;Simmons, 2019;Simmons et al, 2009). This theory links neural noise with an increase in excitatory (e.g., glutamate) synaptic activity and a reduction of inhibitory (e.g., GABA) synaptic activity (e.g., Rubenstein & Merzenich, 2003;Wood et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Previously, we showed that MSPS, a novel situation filled with new information, is a context where young autistic children explore their environment as much as typical children do, thus providing them with similar learning opportunities ( Jacques et al, 2018 ). Current deficit-based autism criteria and theories invoking insistence on sameness, inflexibility (extreme distress in response to changes, difficulties with transitions; APA, 2013 ), sensory hypersensitivity, sensory dysfunction, and/or sensory overload ( Pellicano, 2013 ; Simmons, 2019 ; Sinha et al, 2014 ; Van de Cruys et al, 2014 ), would predict negative emotions in young autistic children who find themselves in a mostly unstructured unfamiliar context including a large array of unfamiliar objects. In the alternative, strength-based accounts of autism involving enhanced perception and perceptual capacity ( Mottron, Bouvet, et al, 2013 ; Mottron et al, 2009 ; Remington et al, 2019 ) suggest that autistics are attracted to information (familiar or not) which they can process well ( Hanley et al, 2017 ), and may benefit from access to more and more complex information of this kind ( Nader et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the perceptual features of autism may be due to variable levels of internal noise, thus leading to difficulties in signal-to-noise separation 39 , 54 59 . Internal noise in autism has been attributed to atypical neural connectivity of sensory brain networks 35 , 37 , 60 , 61 and an imbalance in excitatory and inhibitory neurotransmitters 38 , 62 64 . However, in this study, we found no differences between autistic and control groups in their discriminability indices in both tasks (Figs.…”
Section: Discussionmentioning
confidence: 99%